2009
DOI: 10.1532/hsf98.20091129
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Volume Responders prior to Implantation of a Cardiac Resynchronization Therapy Device via Minithoracotomy: The Septal Flash as a Predictor of Immediate Left Ventricular Reverse Remodeling

Abstract: The preoperative presence of the septal flash is a valid predictor of the response to CRT. Immediately after CRT device activation, the septal flash disappears, and LV reverse remodeling and an increase in contractility are observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Septal flash has recently been a subject of thorough research in patients with heart failure, as it has been reported to be a mechanism to link conduction abnormalities and IVS dyssynchrony in HF [ 5 ]. According to the most recently published data, SF predicts CRT response in patients with permanent atrial fibrillation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Septal flash has recently been a subject of thorough research in patients with heart failure, as it has been reported to be a mechanism to link conduction abnormalities and IVS dyssynchrony in HF [ 5 ]. According to the most recently published data, SF predicts CRT response in patients with permanent atrial fibrillation [ 6 ].…”
Section: Discussionmentioning
confidence: 99%